Burkitt leukaemia/lymphoma: R-CODOX-M/R-IVAC remains gold standard treatment in BL. (November 2016) - Smyth, L.; Browne, P.; Conneally, E.; Flynn, C.; Hayden, P.; Jeffers, M.; O'Brien, D.; Quinn, F.; Kelly, J.; Perera, M.; Crotty, G.; Leahy, M.; et al.
Abstract Background Sporadic Burkitt lymphoma (BL), characterised by translocation-associated C-MYC upregulation is a rare, aggressive lymphoma with a cure rate up to 90 % using the R-CODOX-M/R-IVAC (RCRI) protocol. RCRI is active in HIV-associated BL in combination with HAART. The WHO classification system defines lymphomas intermediate between DLBCL and BL, in which lymphomas with t(14;18)(q32;q21) and C-MYC-carrying translocation, i.e. 'double-hit' are included (BL-DH), and these patients are conventionally treated with RCRI. Result We describe the SJH experience of 25 patients with BL, BL + HIV and BL-DH treated with RCRI between 2002 and 2011. Twelve BL patients (8M/4F), median age 49.1 years (range 20–73 years); of whom 9 had extensive disease, including 8 with marrow and 2 with CNS involvement. Eleven patients remain in remission at 80.5 months (range 37–147 months) from completion of treatment and one died of progressive BL giving an OS of 91.6 % at 1 year with no late relapses. Eight patients with BL + HIV were treated (6M/2F) with a median age 40.25 years (range 24–64). Five remain in complete remission (CR) at 65 months (range 13–109 months), three patients died, two of progressive disease and one of treatment-associated hepatotoxicity in CR. Five patients with BL-DH were included; (3M/2F), age 47.8 years (range 42–55 years); and all patients died of progressive disease, 4 on RCRI therapy and a further patient despite an allogeneic transplantation. Conclusion These results confirm that RCRI is an effective treatment in adults with BL and BL + HIV and remains the gold standard against which other regimens should be compared. We confirm the poor prognosis found in BL-DH, indicating new treatment approaches are needed for this sub-group which should be identified at diagnosis by FISH analysis.